Analysis of Court Decisions on Default in Down Payment Guarantee - Muchtolip Muchtolip (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The development process in Indonesia is currently divided into various sectors, including the economic sector, education and infrastructure. The massive infrastructure development carried out by the Government is carried out in order to support the improvement of public services. Policies related to infrastructure development are currently also simplified, so that more small and large businesses can participate in infrastructure tenders. One of these policies is the Down Payment Guarantee Policy. Down Payment Guarantee is a guarantee provided by an insurance company that guarantees that the company is able to carry out a project and can return the down payment according to the agreed rules. In its implementation, it turns out that the Down Payment Guarantee can experience disputes and lead to claims for Default. This study will analyze court decisions in cases of Default claims in Down Payment Guarantee cases. The approach used in this study is normative juridical law.